ANALISIS KOMPONEN UTAMA UNTUK MENGETAHUI FAKTOR DOMINAN YANG MEMPENGARUHI ANGKA KEMISKINAN (Studi Kasus di Kabupaten Banyuwangi) - Feby Indriana Yusuf; Heri Susanto (Mathematics Department of Mathematics and Natural Sciences Unisda Lamongan, 2017)
The poverty rate is an important component for improvement of Banyuwangi. The declining poverty rate is an indicator that Banyuwangi people have improved the welfare and better quality region. The dominant factors causing poverty need to be the main concern of Banyuwangi government to suppress and reduce poverty. Factor analysis is used as a method in determining the dominant factors that influence poverty rate in Banyuwangi. The variables analyzed are level of education ( V1), illiteracy (